2015
DOI: 10.1097/md.0000000000001639
|View full text |Cite
|
Sign up to set email alerts
|

Lower Serum 25-Hydroxyvitamin D Level is Associated With 3 Types of Autoimmune Thyroid Diseases

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
4
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 36 publications
(46 reference statements)
1
56
4
5
Order By: Relevance
“…Every 5 nmol/l decrease in serum 25(OH)D 3 concentrations was associated with a 1.51-fold increase in PPT risk (95% CI 1.25-1.82). However, in this study predelivery calcidiol levels were not associated with TSH, anti-TPO or anti-TG levels (38).…”
Section: Vitamin D Status and Postpartum Thyroiditiscontrasting
confidence: 82%
See 2 more Smart Citations
“…Every 5 nmol/l decrease in serum 25(OH)D 3 concentrations was associated with a 1.51-fold increase in PPT risk (95% CI 1.25-1.82). However, in this study predelivery calcidiol levels were not associated with TSH, anti-TPO or anti-TG levels (38).…”
Section: Vitamin D Status and Postpartum Thyroiditiscontrasting
confidence: 82%
“…However, no difference in the prevalence of vitamin D deficiency (25(OH)D 3 < 20 ng/ml) between 100 patients with AITD (52 HT, 48 GD) and 126 healthy controls was observed by D'Aurizio et al (11). Likewise, the relationship between low vitamin D levels and the presence of anti-TPO and anti-TG antibodies was not always observed (14,37,38,41). Goswami et al in a group of 642 subjects from India revealed only a weak inverse correlation between serum calcidiol and anti-TPO concentrations (r = -0.08, p = 0.04), but no association between vitamin D deficiency (25(OH)D 3 < 10 ng/ml) and anti-TPO positivity (33).…”
Section: Human Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Yasuda et al [23] established that the serum vitamin D level in the group of 26 females, newly diagnosed with GD, was significantly lower than the group comprising of 46 healthy females (p<0.05). Ma et al [24] demonstrated that vitamin D level in 70 patients with newly diagnosed GD was substantially lower than that in the healthy control group. However, in the present study, we did not find significantly decreased vitamin D level in patients newly diagnosed with GD, which was contradictory to the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The results illustrated that NB-UVB therapy has more prominent effects than topical medications. It has also been reported that low serum levels of 25-hydroxyvitamin D are not only related to autoimmune diseases (such as inflammatory bowel disease 20,21 and autoimmune thyroid disease 22,23 ) but also associated with vitiligo. 24,25 Treatment with UVB could improve the serum levels of 25-hydroxyvitamin D, which is another functional mechanism of NB-UVB to treat vitiligo.…”
Section: Systemic and Topical Corticosteroids Have Been Demonstratedmentioning
confidence: 99%